Pengaruh Kepercayaan Diri dan Penguasaan Kosakata terhadap Keterampilan Berbicara Bahasa Inggris Siswa - Maria Adelina (SAP (Susunan Artikel Pendidikan), 2017)
This research aims to show the effects of self-confidence and vocabulary mastery on English speaking skill. The method used in this research is a survey method with correlation technique. It is used to show a correlation between research variables. The sample of this research consists of 138 students from SMAN in East Jakarta, namely SMAN 39 and SMAN 88 in 2014. The result of the research shows that: 1) There are jointly significant effects of self-confidence and vocabulary mastery on English speaking skill, as proven by the value of FO = 11,130 and Sig. 0,000 < 0,05, meaning that self-confidence and vocabulary mastery variables jointly make a contribution of 14.2 % to student’s English speaking skill. 2) There is a significant effect of self-confidence on English speaking skill, as seen by the value of  tO = 3,987 and Sig. 0,000 < 0,05, indicating that self-confidence variable makes a contribution of 9.83% towards improving student’s English speaking skill. 3) There is a significant effect of vocabulary mastery on student’s English speaking skill, as shown by the value of tO = 2,699 and Sig. 0,008 < 0,05, meaning that vocabulary mastery variable makes a contribution of 4,32% towards improving student’s English speaking skill.